RAPID DETECTION OF THE AFRICANIZED HONEY BEE: A TOOL FOR INDONESIAN ANIMAL QUARANTINE - RIKA RAFFIUDIN; ANIFA BINTAR; M. CHANDRA WIDJAJA; AHMAD FARAJALLAH; BAMBANG PURWANTARA (BIOTROPIA, 2009)
Molecular detection methods were used to determine if Africanized Honey Bees (AHBs) are present in populations of imported Apis mellifera in Indonesia. The cytochrome b (cyt b gene) was amplified from mitochondrial DNA and digested with the BglII restriction enzyme (cytb/BglII). Two types of animal DNA extraction kits were used and found suitable for rapid preparation of DNA from A. mellifera by the Animal Quarantine facility. Results showed that all 94 colony samples from beekeepers in Java produced a 485 bp PCR product from the amplification of this gene. Two DNA fragments of 194 and 291 bp from all samples were produced after digestion with BglII. This cytb/BglII result together with the DNA sequence of cyt b showed that all collected samples of A. mellifera were the non-AHB type. Hence, this study did not detect AHB in Indonesia.Key words :Â  Apis mellifera, molecular detection methods, DNA, cytochrome b, mitochondrial genetics